2021
DOI: 10.3390/ani11051321
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Analysis of Major Production and Reproduction Traits of Korean Duroc, Landrace and Yorkshire Pigs

Abstract: The study aimed to investigate the genetic parameters of the production and reproduction traits of Korean Duroc, Landrace, and Yorkshire pigs. Three production traits, namely average daily gain (ADG), age at 105 kg body weight (DAYS105) and backfat thickness (BFT), and three reproduction traits, namely age at first farrowing (AFF), total number of piglets born (TNB) and number of piglets born alive (NBA), were analyzed. The reproduction dataset was based on first-parity gilts only. However, the production data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
18
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 52 publications
3
18
1
Order By: Relevance
“…In this study, we built the cross‐fostering model of Duroc and Yorkshire, to investigate the effect of different but healthy maternal environments on the gut microbiota and even the growth performance of the offspring. Piglets belonging to different breeds showed no significant difference in body weight and ADG on day 28 and day 70, which was consistent with the previous study 19 . However, both ADG and body weight of Dd was significantly lower than Dy and Yd on day 70, which suggested that cross‐fostering may affect the growth performance for a long time.…”
Section: Discussionsupporting
confidence: 90%
“…In this study, we built the cross‐fostering model of Duroc and Yorkshire, to investigate the effect of different but healthy maternal environments on the gut microbiota and even the growth performance of the offspring. Piglets belonging to different breeds showed no significant difference in body weight and ADG on day 28 and day 70, which was consistent with the previous study 19 . However, both ADG and body weight of Dd was significantly lower than Dy and Yd on day 70, which suggested that cross‐fostering may affect the growth performance for a long time.…”
Section: Discussionsupporting
confidence: 90%
“…This finding confirmed the contribution of SGE to total heritable variance. We found that the DUC had lower heritability for ADG than the crossbred pigs, and they also had lower heritability for ADG than other Duroc populations reported previously [ 30 , 31 , 32 , 33 ]. These results suggest that intensive selection events for growth traits have occurred in DUC populations.…”
Section: Resultscontrasting
confidence: 39%
“…Indeed, DUC pigs have been intensively selected for growth traits after they were introduced into South Korea. A recent study reported substantial genetic improvement of ADG in DUC pigs, as the estimated breeding value for ADG has increased from −5.23 g to 45.16 g since 2000 [ 30 ]. Therefore, there may now be less chance for genetic improvement for ADG in the DUC population.…”
Section: Resultsmentioning
confidence: 99%
“…The various BF in different populations might cause by the difference in genetics, breed groups, ages and site at measurement, feed formular, feeding management and environmental conditions (i.e., open-house system or evaporative cooling system) including factors relating feed intake of the pigs. However, gilts in our population (CV 18%) had a slightly lower variation of BF than gilts in Philippines (Lego and Bondoc 2020), South Africa (Dube et al 2011), China (Hu et al 2016) and Korea (Alam et al 2021) which had CV ranged from 18.52 to 19.75% but other Landrace populations in Thailand, they had much higher variation of BF with CV of 25.90% (Imboonta et al 2007) and 28.81% (Wongsakajornkit and Imboonta 2015). The variation of BF in this population was in the range of BF as found in both tropical and temperate countries but more uniformity that implied to the e ciency of feeding program and well management under tropical condition.…”
Section: Discussionmentioning
confidence: 52%